Significance of Teamwork in Organization - Mohanty , Sasmita (International Journal of Psychosocial Rehabilitation, 2019)
An organization as it means is a consciously established social structure to achieve some definite ends. It is made up of a number of people involved in patterned acquaintances. Group training is needed to enhance group-building experience. Team building is the process of helping a working group become more efficient in fulfilling its tasks and meeting the needs of the group members. By looking at university as a social system then a change strategy must aim to change the whole system-not just part of it. Team building has been described as a significant tool for enhancing the psychological environment in which teams work and the overall functioning of the teams. In the sports sense, team-building strategies have been consistently found to contribute to changes in team effectiveness. Team building includes a wide array of practices designed to enhance team performance. Their goal is to bring out the best in a team to ensure self-development, constructive communication, leadership skills and the ability to work together as a problem-solving team together.